Coping With the Emotional Impact of Working in Cancer Care: The Importance of Team Working and Collective Processing - Cotter, Pádraig; Holden, Anneka; Johnson, Caroline; Noakes, Sarah; Urch, Catherine; King, Alex (Frontiers in Psychology, 2022)
Hospitals provide the vast majority of cancer care. A necessary focus on survival has meant that they are less well-developed in terms of supporting patients with the emotional impact of cancer; and in supporting the frontline staff who contend with this. An integration of psychotherapeutic and neurobiological findings is used to develop an understanding of the patient-staff relationship and impact of high levels of distress within it. This includes reference to Transference and Countertransference, Mirror Neurons and Poly Vagal Theory. This paper considers how patients can unconsciously ‘transfer’ emotional distress on to healthcare practitioners; and how this evokes an emotional response from the practitioner via the mirror neuron system. This can allow the practitioner to ‘feel into’ the patient’s experience and develop a more nuanced understanding. However, it may also activate emotions connected to the practitioner’s life and can leave them feeling overwhelmed. The practitioner’s capacity to regulate their own emotional arousal, via the vagus nerve, has a significant impact on their ability to support the patient and themselves within emotionally distressing interactions. This dynamic often unfolds without either party having significant awareness of it. A Systemic and Process-Oriented perspective is taken to understand this within the broader context of a hospital-based structure; and consider how practitioners on frontline teams may or may not support each other in working collectively with high levels of distress. A team’s level of understanding and attunement to emotional experiences as well their primary relational and communication style has significant bearing on capacity for emotion-and-relationship focused coping. A failure to work with the emotional and relational interconnection between patients and staff can contribute to isolated patients, disconnected staff, conflict within teams and an overarching system lacking in compassion. However due to the often unconscious nature of such processes and limited understanding or training on them, they are regularly left unaddressed. Over time, this can have an accumulated effect on everyone. Group-based collective processing is considered in terms of how it can be used in supporting practitioners to integrate an emotional and relational way of working with a problem-focused approach and integrated into regular daily working.